Effective Antibacterial/Photocatalytic Activity of ZnO Nanomaterials Synthesized under Low Temperature and Alkaline Conditions - Sujeong Kim; Hyerim Park; Sadanand Pandey; Daewon Jeong; Chul-Tae Lee; Jeong Yeon Do; Sun-Min Park; Misook Kang (Nanomaterials, 2022)
The purpose of this study was to evaluate the surface properties of ZnO nanomaterials based on their ability to photodegrade methyl blue dye (MB) and to show their antibacterial properties against different types of Gram-positive bacteria (Bacillus manliponensis, Micrococcus luteus, Staphylococcus aureus) and Gram-negative bacteria (Escherichia coli). In this study, ZnO nanomaterials were synthesized rapidly and easily in the presence of 1–4 M NaOH at a low temperature of 40 °C within 4 h. It was found that the ZnO nanomaterials obtained from the 1.0 M (ZnO–1M) and 2.0 M (ZnO–2M) aqueous solutions of NaOH had spherical and needle-shaped forms, respectively. As the concentration of NaOH increased, needle thickness increased and the particles became rod-like. Although the ZnO nanomaterial shapes were different, the bandgap size remained almost unchanged. However, as the NaOH concentration increased, the energy position of the conduction band shifted upward. Photo current curves and photoluminescence intensities suggested that the recombination between photoexcited electrons and holes was low in the ZnO–4M materials prepared in 4.0 M NaOH solution; however, charge transfer was easy. ∙O2− radicals were generated more than ∙OH radicals in ZnO–4M particles, showing stronger antibacterial activity against both Gram-positive and Gram-negative bacteria and stronger decomposition ability on MB dye. The results of this study suggest that on the ZnO nanomaterial surface, ∙O2− radicals generated are more critical for antibacterial activity than particle shape.